Recent advances in fabricating high-performance triboelectric nanogenerators via modulating surface charge density - Li, Zekun; Yu, Aifang; Zhang, Qing; Zhai, Junyi (International Journal of Extreme Manufacturing, 2024)
Triboelectric nanogenerators (TENGs), a type of promising micro/nano energy source, have been arousing tremendous research interest since their inception and have been the subject of many striking developments, including defining the fundamental physical mechanisms, expanding applications in mechanical to electric power conversion and self-powered sensors, etc. TENGs with a superior surface charge density at the interfaces of the electrodes and dielectrics are found to be crucial to the enhancement of the performance of the devices. Here, an overview of recent advances, including material optimization, circuit design, and strategy conjunction, in developing TENGs through surface charge enhancement is presented. In these topics, different strategies are retrospected in terms of charge transport and trapping mechanisms, technical merits, and limitations. Additionally, the current challenges in high-performance TENG research and the perspectives in this field are discussed. Tactics for modulating the surface charge density of TENGs by material optimization are summarized. Strategies for manufacturing ultra-high electrode charge density TENGs utilizing advanced circuit designs are demonstrated. The synergistic effects of material optimization and advanced circuit design are presented. Current challenges in the field of TENGs are discussed.